PROYEKSI PRODUKSI PERKEBUNAN KELAPA SAWIT RAKYAT DI KEPULAUAN BANGKA BELITUNG - Laily Muharani; Nur Khasanah; Priestiani Priestiani; Dewi Tumatul Ainin; Muarto Wijaya (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2025)
Palm oil is a plantation commodity that plays an important role in the development of the national strategic economy. Palm oil plantations contribute significantly to regional income, employment absorption, and downstream industrial development. However, the development of plantations in the Bangka Belitung Islands Province faces challenges, such as limited land, agro-ecosystems that are different from the central areas of palm oil plantation commodity production. This study focuses on the Bangka Belitung Islands Province which was carried out in April 2025, using a time series analysis approach using data on production and area of ​​smallholder palm oil land in a 7-year period (2018-2024) with Simple Linear Regression analysis. Palm oil productivity in the Bangka Belitung Islands tends to increase every year with an average productivity of 2.20 tons/ha. The projection of smallholder oil palm in the Bangka Belitung Islands from 2025 - 2031 has increased annually by 14,160.6 tons/year and an average production of 192,350.2 tons/year, using simple linear regression, the projection equation results are Ft = - 284,404,498 + 14,160.6t.